Risk of high-grade cervical dysplasia and cervical cancer in women with systemic lupus erythematosus receiving immunosuppressive drugs. (June 2017) - Feldman, C H; Liu, J; Feldman, S; Solomon, D H; Kim, S C
Objective: Prior studies suggest an increased risk of cervical cancer among women with systemic lupus erythematosus. However, the relationship with immunosuppressive drugs is not well studied in US nationwide cohorts. We compared the risk of high-grade cervical dysplasia and cervical cancer among women with systemic lupus erythematosus who started immunosuppressive drugs versus hydroxychloroquine. Methods: We identified systemic lupus erythematosus patients initiating immunosuppressive drugs or hydroxychloroquine using claims data from two US commercial health plans and Medicaid (2000–2012). We used a validated claims-based algorithm to identify high-grade cervical dysplasia or cervical cancer. To account for potential confounders, including demographic factors, comorbidities, medication use, HPV vaccination status, and health care utilization, immunosuppressive drugs and hydroxychloroquine initiators were 1:1 matched on the propensity score. We used inverse variance-weighted, fixed effect models to pool hazard ratios from the propensity score-matched Medicaid and commercial cohorts. Results: We included 2451 matched pairs of immunosuppressive drugs and hydroxychloroquine new users in the commercial cohort and 7690 matched pairs in Medicaid. In the commercial cohort, there were 14 cases of cervical dysplasia or cervical cancer among immunosuppressive drugs users and five cases among hydroxychloroquine users (hazard ratio 2.47, 95% CI 0.89–6.85, hydroxychloroquine = ref). In Medicaid, there were 46 cases among immunosuppressive drugs users and 29 cases in hydroxychloroquine users (hazard ratio 1.24, 95% CI 0.78–1.98, hydroxychloroquine = ref). The pooled hazard ratio of immunosuppressive drugs was 1.40 (95% CI 0.92–2.12). Conclusion: Among women with systemic lupus erythematosus, immunosuppressive drugs may be associated with a greater, albeit not statistically significant, risk of high-grade cervical dysplasia and cervical cancer compared to patients receiving hydroxychloroquine alone.